THE USE OF EDUCANDY APPLICATION TO ENHANCE VOCABULARY MASTERY OF VII C STUDENTS AT SMP WIDYA SAKTI DENPASAR - Kadek Dwipayanti; I Putu Andre Suhardiana; Ida Bagus Gde Phalaguna (Yavana Bhasha : Journal of English Language Education, 2025)
This study aims to know the best implementation of Educandy Application combined with problem – based learning method to enhance vocabulary mastery of VII C students at SMP Widya Sakti Denpasar. The subject of this research was 35 students of VII C class. This research used Classroom Action Research as research design in which consist of 2 cycles with 2 meetings in each cycles. The instrument of this study is vocabulary test that conducted in preliminary study, cycle I and cycle II. The success criteria of this research is, if all of VII C students passed the minimum completion criteria score which was 75. The finding showed that there is an improvement in students' vocabulary mastery based on the test results. In cycle I, the average score of students was 75 and in cycle II it increased to 87. In addition, the number of students who passed the minimum completion criteria score also increased, from previously in cycle I there were only 18 students while in cycle II, 35 students or all students of class VII C succeeded. The best implementation of Educandy application combined with the problem-based learning method in improving students' vocabulary mastery is by using its features such as crossword and word search game to introduce problem to the students. On this step of problem – based learning, the teacher supposed to introduce the problem to be discussed, then to keep the activity simple, the researcher offered crossword and word search game to be used on this activity.